Combating Commercial Sexual Exploitation Of Children In Medan City - Hanan; Suhaidi; Mahmud Mulyadi; Mahmul Siregar (Mahadi: Indonesia Journal of Law, 2025)
The crime of commercial sexual exploitation of children has become a major issue both nationally and internationally because it is considered a gross violation of human rights. Indonesia is one of the countries that is committed to combating the commercial sexual exploitation of children. It is reported that North Sumatra is one of the senders and receivers of the trafficked children. Medan, one of the cities in North Sumatra is included in the category of sender and recipient. This is supported by the geographical location of Medan which is very strategic as the capital of North Sumatra province. Based on this, the problems discussed in this research were: 1) How to manage the child protection from commercial sexual exploitation of children in accordance with the laws and regulations in Indonesia; 2) What response to commercial sexual exploitation of children in Medan was; 3) What obstacles found in the prevention of commercial sexual exploitation of children in Medan were. This research used descriptive analytical method with juridical normative approach by describing how the commercial sexual exploitation of children (CSEC) happened and how to overcome it. The legal source materials used were primary, secondary, and tertiary legal materials. The results showed that the regulations of commercial sexual exploitation of children have been regulated generally on national and international scale. Crime prevention efforts against sexual exploitation of children in Medan was based on two approaches, penal and non-penal policy. It could be seen from the penal policy of the Court Verdicts No. 1554/Pid.B/2012/PN.Mdn and No. 2743/ Pid.B/2006/PN.Mdn in which the defendants were found guilty. But it seemed that the sentences did not meet the elements of justice. While in the non-penal policy, some efforts to prevent were applied in Medan, such as preventive and repressive supervision and handling the CSKA. There were three obstacles found in the prevention of CSEC; in terms of legislation, law enforcement officials, and culture.